Congestive heart failure, obstructive sleep apnea, and chronic obstructive pulmonary disease – Triple Overlap Syndrome - G. Voynova; P. Kalaydzhiev; R. Ilieva; G. Nikolova; D. Markov; S. Yakov; Ts. Kotsev; N. Georgieva; A. Hristova; L. Shopov; E. Kinova; A. Goudev (Българска кардиология)
The individual approach in the treatment of heart failure (HF) and personalized medicine have been the main topic in recent years in all scientific forums. The combination of chronic obstructive pulmonary disease (COPD) and sleep apnea (SA) further complicates the clinical presentation in patients with HF. The overlap of all three diseases requires a team of specialists and additional therapeutic approach for better control and to improve the prognosis. A large number of the pathophysiological mechanisms of the three diseases also overlap. The novel therapies for HF have shown good results, both in COPD and CA subgroups. Noninvasive ventilation during hospitalization and at home is an established method in the individual groups. In a combination of the three diseases, definitive data from randomized trials are still lacking.